On Parameterized Time Neutrosophic Soft Set and its Aplication (European Journal of Pure and Applied Mathematics, 2025)
In his doctoral dissertation, Ayman A. Hazaymeh presented the idea of time-fuzzy soft set in 2013, which is an extension of fuzzy soft set[1]. In this work, we present the idea of the parameterized time neutrosophic soft set, which is an extension of the neutrosophic soft set, and examine some of its characteristics. Its fundamental operations, complement, union, intersection,”AND,” and ”OR,” are also defined, and their characteristics are examined. We also provide a fictitious example of how this idea may be used in decision-making issues.